Expression of the Circadian Clock Gene BMAL1 Positively Correlates With Antitumor Immunity and Patient Survival in Metastatic Melanoma - de Assis, Leonardo Vinícius Monteiro; Kinker, Gabriela Sarti; Moraes, Maria Nathália; Markus, Regina P.; Fernandes, Pedro Augusto; Castrucci, Ana Maria de Lauro (Frontiers in Oncology, 2018)
Introduction Melanoma is the most lethal type of skin cancer, with increasing incidence and mortality rates worldwide. Multiple studies have demonstrated a link between cancer development/progression and circadian disruption; however, the complex role of tumor-autonomous molecular clocks remains poorly understood. With that in mind, we investigated the pathophysiological relevance of clock genes expression in metastatic melanoma. Methods We analyzed gene expression, somatic mutation, and clinical data from 340 metastatic melanomas from The Cancer Genome Atlas, as well as gene expression data from 234 normal skin samples from genotype-tissue expression. Findings were confirmed in independent datasets. Results In melanomas, the expression of most clock genes was remarkably reduced and displayed a disrupted pattern of co-expression compared to the normal skins, indicating a dysfunctional circadian clock. Importantly, we demonstrate that the expression of the clock gene aryl hydrocarbon receptor nuclear translocator-like protein 1 (BMAL1) positively correlates with patient overall survival and with the expression of T-cell activity and exhaustion markers in the tumor bulk. Accordingly, high BMAL1 expression in pretreatment samples was significantly associated with clinical benefit from immune checkpoint inhibitors. The robust intratumoral T-cell infiltration/activation observed in patients with high BMAL1 expression was associated with a decreased expression of key DNA-repair enzymes, and with an increased mutational/neoantigen load. Conclusion Overall, our data corroborate previous reports regarding the impact of BMAL1 expression on the cellular DNA-repair capacity and indicate that alterations in the tumor-autonomous molecular clock could influence the cellular composition of the surrounding microenvironment. Moreover, we revealed the potential of BMAL1 as a clinically relevant prognostic factor and biomarker for T-cell-based immunotherapies.